The regulon of Brucella abortus two- component system BvrR/BvrS reveals the coordination of metabolic pathways required for intracellular life - Rivas-Solano, Olga (2022)
Brucella abortus is a facultative intracellular pathogen causing a severe zoonotic disease worldwide. The two-component regulatory system (TCS) BvrR/BvrS of B. abortus is con- served in members of the Alphaproteobacteria class. It is related to the expression of genes required for host interaction and intracellular survival. Here we report that bvrR and bvrS are part of an operon composed of 16 genes encoding functions related to nitrogen metabolism, DNA repair and recombination, cell cycle arrest, and stress response. Synteny of this geno- mic region within close Alphaproteobacteria members suggests a conserved role in coordi- nating the expression of carbon and nitrogen metabolic pathways. In addition, we performed a ChIP-Seq analysis after exposure of bacteria to conditions that mimic the intracellular environment. Genes encoding enzymes at metabolic crossroads of the pentose phosphate shunt, gluconeogenesis, cell envelope homeostasis, nucleotide synthesis, cell division, and virulence are BvrR/BvrS direct targets. A 14 bp DNA BvrR binding motif was found and investigated in selected gene targets such as virB1, bvrR, pckA, omp25, and tamA. Under- standing gene expression regulation is essential to elucidate how Brucella orchestrates a physiological response leading to a furtive pathogenic strategy.